On the bounded solutions of a difference equation with variable operator coefficient - Gorodnii М.F.; Gonchar, I.V. (Reports of the National Academy of Sciences of Ukraine, 2016)
We study the problem of existence of the unique bounded solution of a difference equation with variable operator coefficient in a finite-dimensional Banach space.